Population dynamics and feeding habit of Oreochromis niloticus and O. mossambicus in Siombak Tropical Coastal Lake, North Sumatra, Indonesia: Population Dynamics and Feeding Habit of Tilapia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Muhtadi A, Nur M, Latuconsina H, Hidayat T. 2021. Population dynamics and feeding habit of Oreochromis niloticus and O. mossambicus in Siombak Tropical Coastal Lake, North Sumatra, Indonesia. Biodiversitas 23: 151-159. Nile Tilapia (Oreochromis niloticus) and O. mossambicus (Mozambique Tilapia) are economically important fish species in Indonesia. This study aims to determine these two fish species' population dynamics, including growth, reproduction, recruitment, mortality rates, exploitation rates, and feeding habits. Samples were taken from September 2018 to August 2019 in Siombak Lake, North Sumatra Province. Data were analyzed in this study using software FISAT-II and Microsoft Excel. The results showed that Nile Tilapia had an isomeric growth pattern, and Mozambique Tilapia exhibited a negative allometric growth pattern. The estimate von Bertalanffy's growth parameters on ELEFAN-I were asymptotic length (L?) of Nile tilapia: 36.06 cm and Mozambique tilapia: 26.09 cm. The growth coefficient (K) of Nile tilapia was 0.59, and Mozambique tilapia was 0.54. The mortality rate (Z) of Nile tilapia reached 3.20 per year, and Mozambique tilapia reached 3.04 per year, whereas the natural mortality (M) of Nile Tilapia 1.24 while Mozambique Tilapia was 1.27. Based on the rate of exploitation, both fish have been overexploited. Peak spawning of Nile Tilapia was in August and December, and of Mozambique Tilapia was in March and June. Both species were omnivores, predominantly with herbivorous feeding habits.
Keywords: Cichlid, estuary, food habit, population structure, tidal lake